2012
DOI: 10.1002/ep.11713
|View full text |Cite
|
Sign up to set email alerts
|

An examination of historical air pollutant emissions from us petroleum refineries

Abstract: Criteria and hazardous air pollutant emissions from petroleum refineries in the US have decreased over the last 20 yr despite increasing crude density, changes in sulfur concentrations, increasingly stringent product specifications, and overall increase of refinery production of major fuel types. Refinery emissions of criteria air pollutants have decreased as much as 80% from 1990 to 2010. Emissions of hazardous air pollutants and their associated toxicity hazard potential have decreased nearly 70%. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Petroleum (crude oil) is the origin of many complex mixtures such as petrol and diesel fuel and is, via chemical processes, used to produce plastics and other useful materials such as textiles [ 2 ], pesticides, cosmetics, paints, and insulating materials [ 3 ]. Workers in the petroleum industry are exposed to a variety of known or potentially harmful substances [ 4 ] and emissions from oil and gas extractions are among the major sources of air pollution in environments and communities where such facilities are situated and operate [ 5 , 6 , 7 ]. These potential harmful exposures include, among others, heavy metals and hydrocarbons such as benzene which is up to 4 g/L in crude oil [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Petroleum (crude oil) is the origin of many complex mixtures such as petrol and diesel fuel and is, via chemical processes, used to produce plastics and other useful materials such as textiles [ 2 ], pesticides, cosmetics, paints, and insulating materials [ 3 ]. Workers in the petroleum industry are exposed to a variety of known or potentially harmful substances [ 4 ] and emissions from oil and gas extractions are among the major sources of air pollution in environments and communities where such facilities are situated and operate [ 5 , 6 , 7 ]. These potential harmful exposures include, among others, heavy metals and hydrocarbons such as benzene which is up to 4 g/L in crude oil [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The difference might be caused by the changes in refinery operations and practices in the past decades, as the catalyst coke EF in AP-42 reflects refinery practices in 1960s–1970s, while the results from the present study reflect U.S. refinery practice in 2014. A study by Nelson and Nguyen shows that U.S. refinery CAP emissions decreased by 46–91% from 1990 to 2013 with the application of emission control technologies. Another factor that could contribute to catalyst coke SO 2 reduction is the increased application of gas oil hydrotreating, which reduces the sulfur content of FCC unit feedstock.…”
Section: Results and Discussionmentioning
confidence: 99%
“…One study conducted for the American Fuel & Petrochemical Manufacturers organization by Nelson and Nguyen shows that NO x pollutant per crude input in refineries decreased to 100 g NO x /m 3 crude in 2011. The present study shows NOx emission of 2.32 g/MJ (84 g/m 3 ) crude in 2014, comparable with the results from the Nelson and Nguyen study.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an events are causing more concern and people are thinking about the consequences and effects of process accidents in industrial activitie [7]. A study conducted in the field of energy in recent years [8][9][10][11] indicated that accidents caused by explosions and fires in the oil industry accounted for 25% of the total economic losses. It is in the second place, after nuclear energy.…”
Section: Introductionmentioning
confidence: 99%